Occupied Europe and German art historiography: methodology and morals - Arnold Witte (Journal of Art Historiography, 2017)
Review of Kunstgeschichte in den besetzten Gebieten 1939-1945, edited by Magdalena Bushart, Agnieszka Gasior and Alena Janatkova. Cologne/Weimar/Vienna: Böhlau, 2016. The art historiography of the period of German National-Socialism has made significant methodological progress in the last two decades, and the present volume widens the geographical scope to include the territories occupied between 1939 and 1945 by the German army. How did art historians in these countries respond to the expectations and demands of these new authorities? A range of studies on Czech, Polish, Dutch, Belgian and Lithuanian academics shows how they were either lured into cooperation with the Germans on the basis of ‘Aryan’ concepts of art and culture, or ostracized when not considered part of the German race. A range of other essays on German art historians show how they were actively involved in propaganda activities in occupied countries. Notwithstanding its geographical bias towards eastern Europe, this volume shows how important this exchange was for the course of the discipline in various regions, and that using archival research is a sine-qua-non for the study of art historiography in times of regime change.